2012
DOI: 10.1016/j.eneco.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The globalization of steam coal markets and the role of logistics: An empirical analysis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…As for coking coal, it is a primary constituent in the production of over 70% of the world's steel. The global market for coal, both thermal and metallurgical, is currently estimated to be nearly 8 billion tonnes per year and expected to grow 12.5% by 2035, with the growth in demand centered primarily in Asia (BP Energy Outlook 2016) In line with this numbers, our goal in this paper is dual: show, in agreement with Zaklan et al (2012), that the world coal market continues to be weakly integrated; but is moving East from multiple perspectives.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…As for coking coal, it is a primary constituent in the production of over 70% of the world's steel. The global market for coal, both thermal and metallurgical, is currently estimated to be nearly 8 billion tonnes per year and expected to grow 12.5% by 2035, with the growth in demand centered primarily in Asia (BP Energy Outlook 2016) In line with this numbers, our goal in this paper is dual: show, in agreement with Zaklan et al (2012), that the world coal market continues to be weakly integrated; but is moving East from multiple perspectives.…”
Section: Introductionmentioning
confidence: 78%
“…Using multiple methods including cointegration tests and the Kalman filter, with monthly FOB export data in six countries (Australia, China, Colombia, Indonesia, Poland andSouth Africa) between 1995-2007, they conclude that, in general, the international steam coal market could be seen as integrated over that time period. Zaklan et al (2012) add the logistics perspective and analyze the integration of international steam coal trade using weekly import, export and transportation data from 2001 to 2009. They use a principal component analysis (PCA) and Johansen cointegration tests and concluded that there was a significant, yet incomplete, integration.…”
Section: World Coal Markets Outlook and Literature Overviewmentioning
confidence: 99%
“…Taking into consideration the progressive globalization of energy markets (Zaklan et al, 2012;Papież and Śmiech, 2013) reference to the role of Polish mining enterprises in the international energy markets is made by analyzing trends in the consumption of coal in Europe. At the end of the paper, there is a proposal of further pro-effective restructuring activities to apply within the examined enterprises.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of studies have been conducted with the aim to analyze the level of internationalization in energy markets. By relying primarily on results from cointegration analysis, the general consensus is that the crude oil market for all practical purposes can be seen as fully globalized [32] and the same is mainly true for coal markets [33]. Natural gas markets, which hitherto have been very dependent on fixed physical infrastructure in the form of pipelines, are more regionalized, although the increased trade in LNG (liquefied natural gas) will likely lead to an increasingly global natural gas market [34].…”
Section: Using Cointegration Analysis To Assess Geographical Market Imentioning
confidence: 99%